Chemical methods to synthesize FeTiO3 powders - Mona, J.; Kale, Sangeeta N.; Gaikwad, A. B.; Murugan, A. Vadivel; Ravi, V. (Materials Letters, 2006)
Three different techniques were used to synthesize FeTiO3 powders. The first method is simple coprecipitation of both Fe and Ti ions under basic conditions using standard ammonia solution from aqueous ferric nitrate and titanium oxy chloride. This precipitate on heating at 400 degrees C produces ilmenite phase. The second method is to digest hydroxide precipitates at 100 degrees C to form FeTiO3 phase. The third technique is to make use of citrate process to form FeTiO3 powders. The phase contents and lattice parameters were Studied by powder X-ray diffraction (XRD). Particle size and morphology were studied by Transmission Electron Microscopy (TEM). (c) 2005 Elsevier B.V. All tights reserved.
Keywords: Chemical synthesis; Electron microscopy; electronic materials; X-ray methods

La0.7Sr0.3MnO3 nanoparticles coated with fatty amine - Rajagopal, Rajashree; Mona, J.; Kale, Sangeeta N.; Bala, Tanushree; Pasricha, Rem; Poddar, P.; Sastry, M.; Bhagavatula L. V. Prasad; Kundaliya, Darshan C.; Ogale, S. B. (Applied Physics Letters, 2006)
We report on the synthesis of La0.7Sr0.3MnO3 (LSMO) nanoparticles having perovskite structure and particle size of the order of 30 rim. The process involves citrate-gel synthesis, size filtering, and; surface coating with a shell of octadecyl amine (ODA) using electrostatic interaction-assisted novel chemical route. Magnetic measurements show the Curie temperature of similar to 360 K establishing the desired stoichiometry and phase. Fourier transform infrared-studies bring out. that the amine group of ODA interacts with the LSMO surface. Refluidization yields uniform redispersion of the coated and dried powder. (c) 2006 American Institute of Physics.

Synthesis of La0.7Sr0.3MnO3 at 800 degrees C using citrate gel method - Ravi, V.; Kulkarni, S. D.; Samuel, V.; Kale, Sangeeta N.; Mona, J.; Rajgopal, R.; Daundkar, A.; Lahoti, P. S.; Joshi, Rakesh S. (Ceramics International, 2007)
Manganite systems have been of considerable interest in the recent past due to their potential to operate in wide property range and also to serve as effective magnetic sensing and storing devices when synthesized using stringent conditions. We report a novel citrate gel method, in which La0.7Sr0.3MnO3 system has been synthesized at temperature 800 degrees C (LSMO800) with the synthesis duration is 6 h. The results have been compared with the sample synthesized at 1050 degrees C (LSMO1050). The synthesized bulk polycrystalline sample shows single-phase nature with the increase in particle size from similar to 50 nm to 300 nm with the increase in the sintering temperature. The magnetization data for LSMO800 shows well-defined hysteresis with saturation magnetization at around 1800 Oe and Curie temperature at 360 K, which is slightly lower than that of LSMO1050, which is 375 K. The results can be well attributed to the grain boundary effects. (C) 2006 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Ceramics; Citrate gel method; CMR; Oxides

Anomalous microwave heating effects in Ce-doped La(0.7)Sr(0.3)MnO(3): possible role of grain boundary capacitative effects across cerium solubility limit - Kale, Sangeeta N.; Mona, J.; Lofland, S. E.; Kulkarni, S. D.; Ogale, Satishchandra B. (Applied Physics Letters, 2008)
Ce-doped manganite bulk nanocompacts [La(0.7-x)Ce(x)Sr(0.3)MnO(3) (0 < x < 0.1)] are studied for their microwave heating properties at 2.45 GHz. The heating effect is found to be nonmonotonic as a function of cerium concentration, and anomalously large heating (burning) is observed for a small concentration window near x=0.03. The x-ray diffraction studies show signatures of CeO(2) phase in x>0.03 samples. The various characterizations collectively point to the key role of the developing grain boundary CeO(2) layer which leads to highest capacitative intergrain-coupling and related charging-discharging effects when it is thinnest near the apparent Ce solubility limit of x similar to 0.03. (c) 2008 American Institute of Physics.

La0.67Ce0.03Sr0.3MnO3-coupled microwave assisted ultra-fast synthesis of nanocrystalline cobalt oxide and Bismuth oxide - Rajagopal, Rajashree; Mona, J.; Joshi, Rakesh S.; Kale, Sangeeta N.; Pradhan, Sivararn; Gaikwad, A. B.; Ravi, V. (Materials Letters, 2008)
Bismuth hydroxide and Cobalt hydroxide gels were freshly prepared by adding aqueous sodium hydroxide to their corresponding nitrates under basic conditions. Then they were oven dried at 373 K and found to be amorphous in X-ray diffraction (XRD) study. They crystallized into their respective oxides by microwave irradiation (2.45 GHz) in merely 2 min using La0.67Ce0.03Sr0.3MnO3 (LCSMO) as couplant in a microwave domestic oven (similar to 100 W). This is the lowest temperature treatment and synthesis time so far reported in the literature for the formation of these systems. Formation of nanocrystallites of Bi2O3 (10 nm) and Co3O4 (15 nm) has been confirmed by XRD. Normally these hydroxides produce oxides only on heating at temperature >673 K or digesting them at 373 K for 4 - 6 hours as reported by us earlier. Microwave assisted heating proves to be a novel technology whose applications can be carefully harnessed due to its unique effects compared to the conventional heating, such as rapid volumetric heating, shortened reaction time and energy saving. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Citrate gel method; Manganites; Microwave; Oxides

Microwave assisted low temperature rapid synthesis of manganite system using La0.67Ce0.03Sr0.3MnO3 mini-cavity furnace - Kale, Sangeeta N.; Rajagopal, Rajashree; Mona, J.; Londhe, D. P.; Joshi, Rakesh S.; Jagadale, Tushar C.; Satyanarayana, C.; Ravi, V. (Materials Letters, 2008)
Amorphous La0.7Sr0.3MnO3 (LSMO) and La0.7Ca0.3MnO3 (LCMO) precursor powders synthesized by the citrate gel method at 673 K, have been found to crystallize by microwave irradiation in just 60 s using La0.67Ce0.03Sr0.3MnO3 (Ce-LSMO) as couplant. This is the lowest temperature treatment and synthesis time so far reported in literature for the fort-nation of manganite systems. Using ceramic route, the same amorphous samples crystallize on heat treatment only at temperatures greater than 1000 K. The microwave heating through this method is novel and has tremendous potential for accelerating the evolution of the product phase in very shorter durations, with just low temperature processing of the precursors, which cannot be realized in normal process. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: Citrate gel method; LSMO; Manganites; Microwave; Oxides